Cardiac arrhythmias in pregnancy - Mkoko, Philasande; Chin, Ashley (SA Heart Journal, 2022)
Cardiac arrhythmias are common in pregnancy. The approach to the diagnosis of arrhythmias in pregnancy requires a detailed clinical history and examination and documentation of the arrhythmia preferably on a Holter or electrocardiogram. Treatment of arrhythmias is arrhythmia specific and may require antiarrhythmic drug therapy. However, the risks and benefits of antiarrhythmic drugs must be carefully considered. Catheter ablation remains a treatment option but is seldom required during pregnancy.